The Regulation of Drugs in Plato’s Laws - Londoño Sanz, David (2023)
In the standard manuscript of the Laws —the Parisinus Graecus 1807 of the 9th Century AD— this dialogue is placed between the Minos and the Epinomis. While in the Minos the pupil refers to the diversity of rites and traditions that can be observed amongst different peoples, the Epinomis stresses the unity of the law. The regulation of symposia, the access to drugs, to intoxicating drinks and to medicine is a fundamental theme of the Laws. This is evident already from the composition of the dialogue, since this theme is discussed in its first books. The art of regulating communal life is shown as a technique that can be perfected through dialogue. Communal drinking can be beneficial, says the anonymous Athenian foreigner, since wine encourages citizens to sing, and through the confrontation with pleasure citizens are able to exercise temperance. Since the consumption of wine may also produce excesses and loss of constraint, its consumption should be regulated. The Athenian proposes a minimal age limit for wine drinking: 18 years old (Laws, 2.666a-e). The position of the Athenian foreigner concerning the regulation of drugs is a message that might be called “antiprohibitionist”, although not in the contemporary sense (individualist and liberal), but in the sense that an absolute prohibition of drug consumption for the citizens is not defended: the proposal is to allow its consumption, but under a legal and communitarian regulation.